2021
DOI: 10.1111/jnc.15370
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid fisetin reverses impaired hippocampal synaptic plasticity and cognitive function by regulating the function of AMPARs in a male rat model of schizophrenia

Abstract: Cognitive deficits are the core feature of schizophrenia and effective treatment strategies are still missing. Previous studies have reported that fisetin promotes long-term potentiation (LTP) and cognitive function in normal rodents and other model animals of neurological diseases. The aim of this study was to assess the effect of fisetin on How to cite this article: Zhan J-Q, Chen C-N, Wu S-X, et al.Flavonoid fisetin reverses impaired hippocampal synaptic plasticity and cognitive function by regulating the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(105 reference statements)
1
7
0
1
Order By: Relevance
“…Fisetin is recommended to be active therapeutic in many disorders, including neurological diseases, while its role in SAE is still unclear. 16 , 17 , 18 , 19 In this study, we confirmed the neuroprotective effects of fisetin on cognitive deficits caused by SAE. Furthermore, we explored the potential mechanism of fisetin on SAE, which might be relevant to increased mitophagy, scavenged ROS, inactivated NLRP3 inflammasome in CMECs, along with decreased caspase‐1 levels, and reduced secretion of IL‐1β into CNS.…”
Section: Discussionsupporting
confidence: 81%
“…Fisetin is recommended to be active therapeutic in many disorders, including neurological diseases, while its role in SAE is still unclear. 16 , 17 , 18 , 19 In this study, we confirmed the neuroprotective effects of fisetin on cognitive deficits caused by SAE. Furthermore, we explored the potential mechanism of fisetin on SAE, which might be relevant to increased mitophagy, scavenged ROS, inactivated NLRP3 inflammasome in CMECs, along with decreased caspase‐1 levels, and reduced secretion of IL‐1β into CNS.…”
Section: Discussionsupporting
confidence: 81%
“…This flavonoid increases the surface expression of the GluA1 subunit of AMPA receptor. It also continues the phosphorylation of the AMPA receptors, as well as CaMKII, CREB, ERK1/2 ( Zhan et al, 2021 ).…”
Section: Role Of Fisetin In Other Neurological Disordersmentioning
confidence: 99%
“…Fisetin, a substance with wide therapeutic potential, which includes effects on MAPK, NF-κB and PI3K, is a naturally occurring flavonoid compound found in various fruits and vegetables such as strawberries, apples, and onions [219]. Fisetin administration has been shown to have beneficial effects in preclinical animal models of diseases such as Alzheimer's disease, Parkinson's disease, Huntington's disease, dementia, schizophrenia, stroke, traumatic brain injury, and the aging process [220][221][222][223][224][225][226]. This substance evokes a variety of pharmacological effects, such as anti-allergic, cancer-preventive and neuroprotective actions [227][228][229].…”
Section: Fisetin-a Mapk Nf-κb and Pi3k Modulator In Neuropathic Painmentioning
confidence: 99%